2010
DOI: 10.1115/1.4001934
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Catabolic to Anabolic Threshold Due to Single-Cell Static Nanomechanical Stimulation in a Cartilage Biokinetics Model

Abstract: Understanding physicochemical interactions during biokinetic regulation will be critical for the creation of relevant nanotechnology supporting cellular and molecular engineering. The impact of nanoscale influences in medicine and biology can be explored in detail through mathematical models as an in silico testbed. In a recent single-cell biomechanical analysis, the cytoskeletal strain response due to fluid-induced stresses was characterized (Wilson, Z. D., and Kohles, S. S., 2010, "Two-Dimensional Modeling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 57 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…6). Both GAG and collagen concentrations at the steady state are now much higher than those observed in the situations without any loading [22] and with the lowest amount of loading ρ =0.02 (Figs. 2 and 3).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…6). Both GAG and collagen concentrations at the steady state are now much higher than those observed in the situations without any loading [22] and with the lowest amount of loading ρ =0.02 (Figs. 2 and 3).…”
Section: Resultsmentioning
confidence: 93%
“…It was also observed that although the collagen molecule accumulation is very high at about the 1,000th dimensionless time step, its abundance is reduced to a much lower value by the steady state condition. In the case of the other modeled structural molecule GAG, no dramatic change is observed between its peak concentration at the 10,000th dimensionless time step and its steady state values [22]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations